RESPONSE GROWTH AND PRODUCTION OF SWEET CORN (Zea mays saccharata Sturt) AGAINST THE GRANTING OF LIQUID ORGANIC TEMPE WASTE FERTILIZER AND LIQUID BIOLOGICAL FERTILIZER - Yudi Santoso; Meizal ,; Darmawati , (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
The aim of this study was to evaluate response growth and production of sweet corn(Zea mays saccharataSturt) on the provision of tempe waste liquid organic fertilizer and liquid biological fertilizer. This study used a randomized factorial design with two factors, namely Liquid Organic Fertilizer Waste Tempe (T0 = control,T1 = 1 ltr/2 ltr of water/plot, T2 = 2 ltr/2 ltr of water/plot andT3 = 3 ltr/2 ltr of water/plot) and Liquid Biological Fertilizer (A0 = Control,A1 = 5 ml/3 ltr of water/plot,A2 = 10 ml/3 ltr of water/plot,A3 = 15 ml/3 ltr of water/plot) treatment repeated three times. Data were analyzed by using analysis of variance followed by different test Mean according to Duncan (DMRT) at 5% level. The results showed that provision of Liquid Organic Fertilizer Waste Tempe significantly affected plant height parameters between 2 and 4 weeks after planting (WAP), number of leaves (6 WAP)and diameter of the cob after harvesting. Provision of Liquid Biological Fertilizer significantly effected on plant height (4 WAP), stem diameter (6 WAP), leaf area (48 days after planting), cob weight, 100seed weight and diameter of the cob. The interaction between the factors giving of Liquid Organic FertilizerTempe waste and liquid bio fertilizer significantly effected on plant height (4 WAP) and the diameter of the cob after harvesting.Key words: liquid organic fertilizer, liquid biological fertilizer, growth and crop production.